Effect of exposure time of pregnant females guppies, Poecilia reticulata Peters, in 17a-methyltestosterone solution on sex ratio of their offsprings - M. Zairin Junior; A. Yunianti; R.R.S.P.S. Dewi; Kusman Sumawidjaja (Jurnal Akuakultur Indonesia)
ABSTRACT